2010
DOI: 10.15209/jbsge.v5i2.181
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intentions among Business Students in Pakistan

Abstract: The present exploratory study is based on the ‘Entrepreneurial Intention Model’ and has its foundation in ‘Planned Behavioural Theory’. The main focus of the study is on measuring factors affecting Entrepreneurial Intentions among business students in Pakistan. Apart from demographics, the study is particularly focused on personal attraction, perceived social norms and perceived social behaviour. The paper is based on systematic sampling methodology and targets business graduates and nascent entrepreneurs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 7 publications
1
17
0
5
Order By: Relevance
“…Besides prior studies which support the general notion that professional attraction contributes to entrepreneurial intention [10][11][12], also found significant relationship between professional attraction and entrepreneurial intention by using Structural Equation Modeling (SEM). Hence, the following hypothesis is proposed: H 1 : Professional attraction has a positive direct effect on entrepreneurial intention…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Besides prior studies which support the general notion that professional attraction contributes to entrepreneurial intention [10][11][12], also found significant relationship between professional attraction and entrepreneurial intention by using Structural Equation Modeling (SEM). Hence, the following hypothesis is proposed: H 1 : Professional attraction has a positive direct effect on entrepreneurial intention…”
Section: Introductionsupporting
confidence: 54%
“…According to [10], entrepreneurial capacity is significant at conventional level and has positive relationship with entrepr eneurial intention. Based on [12] in Taiwan entrepreneurial intention would be more closely related to entrepreneurial self-capacity, and study has found that entrepreneurial self-efficacy (capacity) has positive relationship with the intention to entrepreneurial [12].…”
Section: Entrepreneurial Capacity and Entrepreneurial Intentionmentioning
confidence: 99%
“…Empirical studies from Asia have appeared in recent years, from China (Bernhofer and Han, 2014;Siu and Lo, 2013), Pakistan (Azhar et al 2010), India (Wei, 2007), and Viet Nam (Tran and Santarelli 2014;Mai, 2016) In Shapero's Entrepreneurial Event Model (Shapero, 1975), it considers firm creation as the result of the interaction among contextual factors, which would act through their influences on the individual's perceptions. Shapero lists three dimensions that determine entrepreneurial intention, namely "Perceived desirability," "Perceived feasibility," and "Propensity to act".…”
Section: Introductionmentioning
confidence: 99%
“…The main factors contributing to this interest was the suffering of industrialized countries from economic recession, high unemployment rates and fluctuation in international trade cycles which most of these countries have not experienced before. This situation has tended to increase the attention paid to the potential role of entrepreneurs (Garavan & O'Cinneide, 1994) as one of the possible solutions to the problems faced by most of the countries because the growth of entrepreneurial activities can help in creating jobs for the society and reducing the unemployment rate (Azhar, Javaid, Rehman & Hyder, 2010).…”
Section: Introductionmentioning
confidence: 99%